The Relationship between Psychopathic Personality Traits and Lying - Dobrow, Jason A. (University of South Florida, 2016)
The current study examined the relationship between psychopathic personality traits and various forms of deception. Through the use of the Elemental Psychopathy Assessment to measure psychopathy, and several different assessment tools to measure deception, including the Multidimensional Deception Inventory (MDI), the relationship between psychopathic personality traits and deception was examined. Using an undergraduate sample of 261 participants at a large research university in the Southeastern United States, the relationship between the aforementioned constructs was explored. Results indicated that the overarching personality traits of Antagonism and Disinhibition were positively related to multiple dimensions of lying behavior. Frequency of lies told, Duping Delight (lies told for enjoyment), and lies told for personal gain/impression management and to avoid disclosing pertinent information were positively related to both Antagonism and Disinhibition. Results point to the need for future study in this area, as limited previous research has looked at the overlap between psychopathic personality traits and deception.